A HYBRID HEURISTIC ALGORITHM FOR INTEGRATED PROBLEM OF MACHINE SCHEDULING AND UNIDIRECTIONAL FLOW PATH DESIGN - Zheng, Yan; Xiao, Yujie; Seo, Yoonho (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
During the past few decades, unidirectional flow path design (UFD) and machines scheduling (MS) problems have been studied separately. However, the separate considerations of UFD and MS cannot guarantee the global optimal solution for the whole production. The reason is that UFD and MS are closely interrelated in the real production situation. This paper is to propose a new integrated model, called iUFD/MS, with the objective of minimizing makespan. In iUFD/MS, UFD andMS problems are simultaneously considered. Due to the high complexity of iUFD/MS, a hybrid heuristic algorithm based on particle swarm optimization is developed to get an optimal or near-optimal solution within a reasonable time period. To validate our integrated model, a set of experiments is solved by applying the proposed solution method and the traditional method, respectively. The result shows that our integratd modelcan efficiently reducemakespan by 9.6% on average.